Fondasi Teologis Pastoral Konseling Pendidikan Agama Kristen di Era Digital - Marselina B; Harpennas Harpennas; Damaris Ba'ba; Meliyani Sinding; Arruan Tasik (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This study examines the theological foundations of pastoral counseling in Christian Religious Education (CRE) within the digital era, emphasizing the integration of Trinitarian theology, adolescent developmental psychology, and the Great Commission in Matthew 28:19–20. Digitalization has reshaped adolescent struggles, introducing challenges such as cyberbullying, social media addiction, and virtual identity crises that demand contextual and transformative pastoral responses. Using a qualitative library research approach, this study synthesizes systematic theology, developmental psychology, and transformative pedagogy to construct a conceptual framework for CRE teachers in guiding the digital generation. Findings reveal that Trinitarian theology provides a holistic foundation: God the Father affirms authentic identity beyond digital validation, Christ the Redeemer restores identity from digital trauma, and the Holy Spirit guides character formation for wise engagement in the digital world. Integrating theology with developmental psychology enables a deeper understanding of the digital generation’s struggles and highlights the need for both theological depth and psychological insight. The proposed framework includes five components: Trinitarian foundation, contextual diagnosis, therapeutic intervention, supportive community formation, and the use of digital media as a ministry tool. This integrative and transformative model aims to foster holistic transformation—cognitive, affective, behavioral, and spiritual—preparing adolescents to become mature disciples who bear witness to Christ in digital spaces.